10.7k views
8 votes
6-8x=7x-10x-24 solve for x

User Striatum
by
5.3k points

1 Answer

7 votes

Answer:

x = 6

Explanation:

Let's solve your equation step-by-step.

6−8x=7x−10x−24

Step 1: Simplify both sides of the equation.

6−8x=7x−10x−24

6+−8x=7x+−10x+−24

−8x+6=(7x+−10x)+(−24)(Combine Like Terms)

−8x+6=−3x+−24

−8x+6=−3x−24

Step 2: Add 3x to both sides.

−8x+6+3x=−3x−24+3x

−5x+6=−24

Step 3: Subtract 6 from both sides.

−5x+6−6=−24−6

−5x=−30

Step 4: Divide both sides by -5.

−5x/-5 = -30 /-5

x=6

User Karatchov
by
4.7k points